2020
DOI: 10.3389/fenrg.2020.00002
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Graphene Nano-Scroll Coated Silicon for High Rate Performance Lithium-Ion Battery

Abstract: Owing to its high specific capacity and abundant reserves, silicon has been considered as a promising anode material for future lithium storage. However, its cycle life is seriously hindered by the huge volume variation and low conductivity. Therefore, it is crucial to effectively and easily prepare silicon anode with excellent performance. Herein, we introduce a simple method to prepare graphene nano-scroll coated silicon nanoparticles (Si@rGONSs) on a large scale. With the open tubular structure and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Figure 2A presents three typical peaks of C1s, N1s, and O1s without any impurities in three samples. The spectrum of C 1s exhibits that the primary characteristic peaks at 284.6, 285.9, and 289.1 eV denote the C-C, C-N, and O-C=O of CNs, MCNs, and BMCNs ( Figure 2B), respectively (Zheng et al, 2014;Chu et al, 2018;Shi et al, 2020). Four obvious peaks of N 1s at 398.4, 399.7, 400.6, and 402.4 eV are related to pyridinic N, pyrrolic N, graphitic N, and oxidized N in Figure 2C (Chen et al, 2016;Liu et al, 2017;Peng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2A presents three typical peaks of C1s, N1s, and O1s without any impurities in three samples. The spectrum of C 1s exhibits that the primary characteristic peaks at 284.6, 285.9, and 289.1 eV denote the C-C, C-N, and O-C=O of CNs, MCNs, and BMCNs ( Figure 2B), respectively (Zheng et al, 2014;Chu et al, 2018;Shi et al, 2020). Four obvious peaks of N 1s at 398.4, 399.7, 400.6, and 402.4 eV are related to pyridinic N, pyrrolic N, graphitic N, and oxidized N in Figure 2C (Chen et al, 2016;Liu et al, 2017;Peng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…While the topic was not explored further in these systems, experiments performed on LCO suggested that much of the gas effect does derive from the initial cycles, which agrees with what is known about gas evolution in the published literature and cell preparation techniques discussed in the patent literature. 25,27,51,[58][59][60][61] To gain better insights into which gases may contribute strongly to fade in LMO and LCO, cycling was performed in a variety of gases. The capacity fade of LMO based cells was found to be most sensitive to CO 2 and CH 4 , but did not behave accordingly when cycled in the presence of equal compositions of both gases.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene nanoscroll (GNS), which is a derivative of graphene with a one-dimensional (1D) tubular structure, has received ever-increasing attention from both academia and industry these days. Owing to its unique 1D topology, GNS exhibits distinct properties from those of pristine graphene by encapsulating various foreign organic or inorganic species into its interior cavity and facilitating the radial expansion of the species to accommodate the increasing volume during the ion intercalation process, along with the open topological structure, leading to wide applications in catalysis, adsorption, environmental protection, ion channels, gas separation, etc. Recently, it was proposed as a promising electrode material for the Li-ion battery due to its unique characteristics and higher Li-ion storage capability than that of commercial bulk graphite. However, in order to integrate its real-life devices with practical applications, rational arrangement of individual two-dimensional (2D) planar-structured graphene layers into specific 1D architectures is necessary for converting the remarkable microscopic characteristics of 1D-GNS into macroscopic properties of practical significance.…”
Section: Introductionmentioning
confidence: 99%